1988
DOI: 10.1128/jvi.62.9.3295-3300.1988
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the regulatory region of the human papillomavirus type 6 genome are generated during propagation in Escherichia coli

Abstract: We analyzed the long control regions (LCRs) of seven human papillomavirus type 6b (HPV-6b) clones, which contained prototype HPV-6b sequences recloned into various plasmid vectors and propagated in different strains of Escherichia coli. Southern blot analysis and DNA sequencing demonstrated three different sequences, each distinct from the published prototype HPV-6b sequence. Two of the plasmids contained insertions of 24 and 94 base pairs (bp) and a 1-bp deletion. Four plasmids contained insertions of 24 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…These additional 94 bp were present after position 7350 and were identical to those observed in an independent isolate and published under the code HPV-6 WV6745 (38). We conclude that this sequence was present in the HPV-6b reference type at the time of isolation and was deleted during amplification, a definite possibility according to the studies of the behavior of HPV-6 sequences in Escherichia coli (37). This 94-bp sequence is apparently identical to the additional 120 bp previously identified by restriction analyses, because no additional sequences were found in the LCR or in the 3Ј segment of the L1 gene.…”
Section: Genomic Sequences Of the Lcrs Of The Hpv-6a Hpv-6bsupporting
confidence: 81%
See 1 more Smart Citation
“…These additional 94 bp were present after position 7350 and were identical to those observed in an independent isolate and published under the code HPV-6 WV6745 (38). We conclude that this sequence was present in the HPV-6b reference type at the time of isolation and was deleted during amplification, a definite possibility according to the studies of the behavior of HPV-6 sequences in Escherichia coli (37). This 94-bp sequence is apparently identical to the additional 120 bp previously identified by restriction analyses, because no additional sequences were found in the LCR or in the 3Ј segment of the L1 gene.…”
Section: Genomic Sequences Of the Lcrs Of The Hpv-6a Hpv-6bsupporting
confidence: 81%
“…The bona fide sequence of the 5Ј segment of the LCR of the HPV-6b reference clone has been a matter of confusion, because this region seems to give rise to frequent mutations in vivo. Furthermore, it has also been claimed that a cloning artifact occurred in the original isolate (7,34,37,55). As judged by restriction fragment analysis, a segment of approximately 120 bp may have become artifactually deleted from the HPV-6b clone that was used to establish the published sequence (51).…”
Section: Genomic Sequences Of the Lcrs Of The Hpv-6a Hpv-6bmentioning
confidence: 99%
“…All of the oligonucleotides used in this study were synthesized on an Applied Biosystems model 380B DNA synthesizer (Biochemistry Biotechnology Facility at the Indiana University School of Medicine). Plasmids were amplified in the BE257recA strain (40) of Escherichia coli and purified by using the Qiagen kit reagents and Q-250 chromatography columns. The sequence of all constructs was verified by dideoxy sequencing using Sequenase kit reagents (United States Biochemical).…”
Section: Methodsmentioning
confidence: 99%
“…mixture of typical HPV6a genomes and HPV6a DNA molecules with a deletion of about 0.3kb located in the long control region. HPV6 DNA molecules showing rearrangements in the long control region have previously been reported in some Buschke-Liiwenstein tumours (Boshart and zur Hausen, 1986;Rando et al, 1986;Kasher and Roman, 1988). The patient died from an invasive laryngeal squamous-cell carcinoma which was not available for virologic studies.…”
Section: Squamous-cell Carcinoma (Lip)mentioning
confidence: 66%
“…HPV54 is only weakly related to the known HPVs, but blot hybridization experiments performed under non-stringent conditions have revealed that this newly recognized type is more related to the genital HPVs than to the cutaneous HPVs. The role of HPV54 in the genesis of the Buschke-Lowenstein tumour from which it was cloned appears unlikely, since it was not found in 9 additional cases, and since it was detected in association with HPV6, a HPV type frequently found in Buschke-Lowenstein tumours (Boshart and zur Hausen, 1986;Rando et al, 1986;Kasher and Roman, 1988). Interestingly, HPV6 DNA sequences were detected as a…”
Section: Pathogenicity Of Hpv Types 54 and 55mentioning
confidence: 99%